249 Splenomegaly and anti-nuclear antibodies are driven by interferon- stimulation of B cells in lupus-like disease. (April 2019) - Keller, Emma J; Patel, Neeva; Patt, Madeline; Nemunaitis, Teddy; Reth, Michael; Sen, Ganes; Jorgensen, Trine
Abstract : Background: Systemic Lupus Erythematous (SLE) is an autoimmune disease of unknown etiology affecting 5 million people worldwide. It is known that 50%–70% of lupus patients present with an interferon-alpha (IFN-) gene signature, and it has been shown in multiple mouse models that lupus-like disease can be abolished by IFN- receptor (IFNAR) gene deficiency. Furthermore, disease can be halted by ablating the main producers of IFN-, the plasmacytoid dendritic cells. Thus, IFN- likely has a causative role in lupus-like disease. Multiple immune cells express IFNAR, but it is not known what the effect of IFN- stimulation is on each cell type and how that stimulation affects symptom presentation. We hypothesize that BIFNAR mice would be specifically protected from splenomegaly, B cell activation, and ANA production, due to IFN-s known ability to enhance the antibody response. Methods: To examine the role of B cell responses to IFN- stimulation in mouse lupus-like disease, we studied B cell specific IFNAR-deficiency (BIFNAR) in the B6.Nba2 spontaneous lupus-like disease model, using flow cytometry, ELISA, qRT-PCR and Immunostainings. We also immunized the mice with NP-CGG or NP-Ficoll in complete Freunds adjuvant to determine the effect of IFNAR-expression by B cells during antibody responses to exogenous antigen. Results: At four months of age, BIFNAR mice displayed slightly reduced spleen sizes, although this decrease was not significant until nine months of age. Furthermore, starting at 4 months of age, BIFNAR mice displayed reduced levels of chromatin specific ANAs along with reduced populations of plasmablasts, plasma cells and activated B cells. All other measures of disease showed no difference including total IgG and IgM production, immune complex deposition and C3 complement fixation in the kidney glomeruli, and glomerular size. Somewhat surprising, antibody responses to T-dependent and T-independent immunizations were also not affected. Conclusions: IFN- stimulation on B cells contributed to splenomegaly, increased B cell activation and differentiation, and subsequent production of chromatin specific ANAs, but had no specific role in the response to exogenous antigen. Thus, IFN- remains a valid therapeutic target for SLE; especially in patients presenting with high ANAs. Funding Source(s): R01AI118774